The role of enlightenment in the modernization of Indian and Kazakh societies - Alipbayeva, B.; Кokeyeva, D. (Journal of Oriental Studies, 2022)
At the beginning of the 20th century, representatives of Indo-Kazakh literature, who initially promoted the idea of enlightenment, wanted to modernize society, calling for this through their works. The evidence offered in the article will be used to determine the cause of this phenomenon. After studying the works of writers from both countries, it was clear that each of them was a sympathizer for his people and an educator who shared their work with them. The educators believed that a person can be changed for the better, and recognized this principle as a new approach. In the Indian and Kazakh societies at that time there was a common historical phenomenon, through revolutionary uprisings people wanted new changes, the century of the emergence of a new direction in the field of literature began. There, those who saw the idea of ​​enlightenment as the power of awakening saw the arena of transformational ideas. Another important philosophical thought of that time was the emergence of sentimentalism, which began to view culture as a spiritual being of man, as literature began to pay more attention to human feelings and experiences. Thus, with the help of works of art, people are instilled with moral values. The Enlightenment viewed literature as a means of educating contemporaries in a new spirit, that is, it had a strong didactic origin. The main desire and goal of the writers of the Enlightenment, writing in a critical realistic style, was to awaken in uneducated people the feeling that they could be the basis of progress. The works of writers who contributed to enlightenment in Indian and Kazakh society continue to be in the spotlight, proving that the topic discussed in this article is still relevant today.